Simulation of soybean growth and yield under northeastern Amazon climatic conditions - de Souza, Paulo Jorge de Oliveira Ponte; Farias, José Renato Bouças; de Melo e Abreu, José Paulo Mourão; Ribeiro, Aristides; da Rocha, Edson José Paulino; Botelho, Marcel do Nascimento; de Sousa, Adriano Marlisom Leão (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to parameterize, calibrate, and validate a new version of the soybean growth and yield model developed by Sinclair, under natural field conditions in northeastern Amazon. The meteorological data and the values of soybean growth and leaf area were obtained from an agrometeorological experiment carried out in Paragominas, PA, Brazil, from 2006 to 2009. The climatic conditions during the experiment were very distinct, with a slight reduction in rainfall in 2007, due to the El Niño phenomenon. There was a reduction in the leaf area index (LAI) and in biomass production during this year, which was reproduced by the model. The simulation of the LAI had root mean square error (RMSE) of 0.55 to 0.82 m2 m-2, from 2006 to 2009. The simulation of soybean yield for independent data showed a RMSE of 198 kg ha-1, i.e., an overestimation of 3%. The model was calibrated and validated for Amazonian climatic conditions, and can contribute positively to the improvement of the simulations of the impacts of land use change in the Amazon region. The modified version of the Sinclair model is able to adequately simulate leaf area formation, total biomass, and soybean yield, under northeastern Amazon climatic conditions.
Keywords: Glycine max; Amazon region; climate models; leaf area index; soybean crop expansion; yield simulation